The Contribution of Localization Management System on Zakat Institution Performance - Mohd Amar Aziz; Badariah Haji Din; Kamaruddin Abdulsomad (International Journal of Supply Chain Management, 2018)
This paper attempts to analyze the concept of localization and its relationship with the psychological performance of zakat. It argued that localization could produce development opportunities from the management decentralization of supply chain in zakat institution. In this study, localization is treated as the mediator, while property rights of zakat and asset specificity performed as the independent factors in determining the performance of zakat. Data from 428 samples of zakat payers reveal that localization was performed as the complementary partial mediation toward the performance of zakat. This is due to the property rights of zakat and the asset specificity have the direct impact on the psychological performance. Hence, further exploration of the innovation in supply chain management, especially on the aspect of decentralization of zakat is needed. This study suggested that development opportunities could be met by applying the concept of localization in the zakat institution.